The performance of the K10, K6 and GHQ-12 to screen for present state DSM-IV disorders among disability claimants - Cornelius Bert LR; Groothoff Johan W; van der Klink Jac JL; Brouwer Sandra (BMC, 2013)
Abstract Background Screening for mental disorders among disability claimants is important, since mental disorders seem to be seriously under-recognized in this population. However, performance of potentially suitable scales is unknown. We aimed to evaluate the psychometric properties of three scales, the 10- and 6-item Kessler Psychological Distress Scale (K10, K6) and the 12-item General Health Questionnaire (GHQ-12), to predict present state mental disorders, classified according to the Diagnostic and Statistical Manual of Mental Disorders, 4thEdition (DSM-IV) among disability claimants. Methods All scales were completed by a representative sample of persons claiming disability benefit after two years sickness absence (n=293). All diagnoses, both somatic and mental, were included. The gold standard was the Composite International Diagnostic Interview (CIDI 3.0) to diagnose present state DSM-IV disorder. Cronbach's α, sensitivity, specificity, positive (PPV) and negative predictive values (NPV), and the areas under the Receiver Operating Characteristic curve (AUC) were calculated. Results Cronbach's alpha's were 0.919 (K10), 0.882 (K6) and 0.906 (GHQ-12). The optimal cut-off scores were 24 (K10), 14 ( K6) and 20 (GHQ-12). The PPV and the NPV for the optimal cut point of the K10 was 0.53 and 0.89, for the K6 0.51 and 0.87, and for the GHQ-12 0.50 and 0.82. The AUC's for 30-day cases were 0.806 (K10; 95% CI 0.749-0.862), 0.796 (K6; 95% CI 0.737-0.854) and 0.695 (GHQ-12; 95% CI 0.626-0.765). Conclusions The K10 and K6 are reliable and valid scales to screen for present state DSM-IV mental disorder. The optimal cut-off scores are 24 (K10) and 14 (K6). The GHQ-12 (optimal cut-off score: 20) is outperformed by the K10 and K6, which are to be preferred above the GHQ-12. The scores on separate items of the K10 and K6 can be used in disability assessment settings as an agenda for an in-depth follow-up clinical interview to ascertain the presence of present state mental disorder.